The Issues of Judicial Independence in Indonesia in Contemplation of Islamic Law - Tomi Agustian; Habiburrahman Habiburrahman; Rama Aryanda (NEGREI: Academic Journal of Law and Governance, 2021)
The judiciary (judicial) is an autonomous power that is unaffected by other authorities, especially the executive branch (president). However, the central to the author's analysis is the establishment of justice with the realization of an independent judicial power as the 1945 Constitution's ideals. "The judicial authority is an independent power to establish justice for the establishment of law and justice," according to Article 24 of 1945 Constitution. This principle was later codified in Article 1 Act No. 48 on the Judicial Authority, which was passed in 2009. In principle, the Supreme Court constitution states that the President's appointment of a Grand Judge is subject to congressional motion, and that the Chief, Deputy Chief, Junior Chief, and Judge of Supreme Court dismissal are also carried out by the President on Supreme Court recommendation, and this was the "loophole" which the President had that would later influence the judge's mental in decision-making. The study used normative and juridical approach to identify a link with the principle of justice in Islam, due to in Islam (either the text of the Qur'an or the Hadith) does not expressly contain the presence of Judicial Authority. The Khalifah (President) has always had the right to appoint and dismiss judges in Islamic judicial bodies. Despite the fact that the judge's appointment and dismissal were made by a Khalifah at the time, the judge remained on Allah's good side. So, when the judge's ruling in the case, it was solely aimed at achieving justice. In conclusion, the President's appointment and dismissal of a judge were obviously inappropriate because they could influence the court's conclusions, distorting the meaning of Article 24 of the 1945 Constitution and demonstrating a lack of independent justice